STRATEGY IMPLEMENTATION OF NATIONAL EDUCATION STANDARDS AT THE POTENTIAL JUNIOR HIGH SCHOOL IN BANDUNG - Yusuf Arifin (Kopertis Region IV Jabar and Banten, 2019)
The purpose of this study was to determine 1) the condition of the existing SMP potential in achieving the National Education Standards (SNP), 2) analyze the gap / gap between the real conditions Potential SMP with National Education Standards, 3) formulate an implementation strategy of the National Education Standards to Potential Junior High School. The unit of analysis in this study is 6 Potential Secondary Schools in the city of Bandung, which are in cluster 1 (1 Junior High School), cluster 2 (2 Junior High School) and cluster 3 (3 Junior High Schools). The results showed the level of the gap between the real conditions Potential Secondary Schools in Bandung with National Education Standards are as follows: standard financing is the largest gap compared with other standard is 59.2%. The next largest gap in a sequence is the standard of infrastructure (46.1%), the standard process (39.6%), the standard assessment (29.7%), teachers and education personnel standards (25%), the standard management (23.3 %), content standards (23.2%), and the smallest value of the average gap is competency standards (11%).